ON RESOLUTION STRATEGIES IN FUZZY LOGIC - Yengoyan, S.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In this paper resolution strategies in fuzzy logic are investigated. Some new deduction strategies are introduced in fuzzy logic, analogous to those of classic logic, aimed to narrow deduction search space. In particular, semantic resolution is redefined for fuzzy logic, and some special cases are considered. The completeness of these strategies is proved.
Keywords: fuzzy logic; resolution strategy; completeness